Humanizing Contract Law: A Human Rights-Based Reinterpretation of Freedom of Contract in Indonesia - Yeni Oktafia (Hang Tuah Law Journal, 2026)
The principle of freedom of contract constitutes a fundamental doctrine in Indonesian private law, rooted in liberal paradigms and the autonomy of individual will; however, in contemporary contractual practice, this principle frequently encounters structural challenges arising from unequal bargaining power, economic domination, and information asymmetry, rendering the promised freedom largely formal and potentially giving rise to substantive injustice. This article examines how the principle of freedom of contract should be interpreted and applied to align with human rights principles, particularly equality, non-discrimination, and the protection of weaker parties. Employing a normative juridical method with statutory and conceptual approaches, the research analyses the Indonesian Civil Code, sectoral regulations concerning consumer protection, labour relations, and digital transactions, as well as relevant legal doctrines and theories. The findings demonstrate that the classical, individualistic understanding of freedom of contract is no longer adequate to address the complexities of contemporary contractual relations. Accordingly, the principle must be reinterpreted through a human rights perspective by placing human dignity at the core orientation of private law. This reinterpretation is articulated through the strengthening of normative, institutional, and educational dimensions, ensuring that freedom of contract functions not merely as an instrument of legal certainty, but also as a mechanism for human rights protection and the realization of substantive justice within the Indonesian private law system.